Injuries and illnesses in a cohort of elite youth alpine ski racers and the influence of biological maturity and relative age: a two-season prospective study - Müller, L.; Hildebrandt, C.; Müller, E.; Oberhoffer, R.; Raschner, C. (Open Access Journal of Sports Medicine, 2017)
Background: Studies on injuries and illnesses involving youth ski racers younger than 15 years are lacking in the literature. The aim of this study was prospectively to assess the incidence, prevalence, and severity of traumatic and overuse injuries, as well as illnesses of elite youth ski racers with regard to sex, biological maturity status, and relative age. Subjects and methods: A prospective, longitudinal cohort design was used to monitor the anthropometrics, training characteristics, traumatic and overuse injuries, and illnesses of 82 elite youth ski racers (51 males, 31 females, age 9-14 years) over 2 consecutive years. The exact training exposure (skiing and athletic) was recorded. Relative age and estimated biological maturity status were assessed. Results: Relatively low injury incidence or prevalence (traumatic, 0.86/1,000 hours of training; overuse, 0.28/1,000 hours) and comparably high illness prevalence (2.4/athlete) were reported. The knee was the most commonly affected body part (traumatic injuries 36.5%, overuse injuries 82%). A high number of bone fractures were revealed (46%), while no stress fractures occurred; 66% of the illnesses were respiratory tract infections. No differences were found between males and females, the differing maturity groups, or relative age quartiles. Early-maturing athletes had comparably low traumatic and overuse-injury rates. Relatively younger athletes had low traumatic injury rates. Conclusion: The injury-prevention measures implemented in the training process of youth ski racers seem to contribute to a low incidence of injury. Biological maturity status should be considered in the training process to prevent injuries in late-maturing athletes.